Age‐related site‐specific modifications in diaphyseal structural properties of the human fibula: Furrows and cross‐sectional geometry. Issue 3 (16th August 2020) - Chevalier, Tony; Tignères, Manon
Abstract: Objectives: Fibular structure is related to locomotor behavior, which allows an exploration of mobility in past human populations with diaphyseal cross‐sectional geometry (CSG). However, bone structure depends on age‐related changes. Nonmechanical alterations can affect biomechanical investigations. In this study, we examined how the cortical area and the variables used as functional markers in the fibular diaphysis (i.e., CSG and furrows) change with aging. We predict classic and specific modifications, and we discuss functional interpretations based on bone structure. Materials and methods: The sample consisted of 124 individuals of known age in whom the fibular furrow depths were measured with calipers. Microcomputed tomography (micro‐CT) scanning of 38 individuals provided CSG (e.g., cortical area, shape index, and robusticity) and fibular furrow indices. CSG was studied at five cross sections taken along the diaphysis. Linear regression analyses and age group comparisons were conducted. Results: The cross‐sectional shape summary by fibular furrows and shape index and the total area did not change with aging; in contrast, the cortical area and the robusticity (Zp ‐std) decreased with age. Discussion: The decrease in robusticity (Zp ‐std) with aging is due to the maintenance of total area, which is related to the specific mechanical environment of the fibula, and to the loss of cortical bone and not to the decrease in mechanical stress. This finding is consistent with the lower bone modeling capacity in aged individuals, which also explains the lack of significant changes in the diaphyseal shape. Thus, fibular structure in older individuals is due to a combination of early bone adaptations to stress and aging effects.